Study of making clam shell crusher - Agel Alerta Fadholy; Desmelati '; Dahlia ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research aimed to evaluate the effectiveness of clam shell crusher(Fadholy model). A set of equipment consists of a metal bucket (25 cm indiameter and 22 cm in height), mortar stick which was pushed by a propulsionerpedal, and poles (35 cm in height) all of the component were made of iron with 32kg of total weight. This equipment was designed to capable crushing the shell upto 1,5 kg with crushing frequency 70 times per minute. The effectiveness of theequipment was evaluated for it capability to produce clam shell flour for 1 hour.About 500 grams of dried clam shell was put into a crushing bucket and crushedfor 1 hour. The clam shell flour produced was weighed and filtered through filtersize of 210 microns. The result indicated that the equipment was capable ofproducing clam shell flour up to 99% of the total dried clam shell weight.Keywords : Crusher equipment , Clam shell